Crystal structure, morphology of band-gap engineered Titania and Titanates via hydrothermal synthesis - Lim, Linda Ying Wen (2013)
Titania-based compounds are widely studied for applications in photocatalysis and photovoltaics. In this study, TiS2-derived titania and titanate products are synthesized at various pH of reacting medium under low temperature hydrothermal synthesis. [1st Award]